A Study of The Relationship Between Nutritional Status and Scholastic Achievement Among Primary School Students in Wadi Eldawasir City in Kingdom of Saudi Arabia - Elsayead, Manal Abd Elaleim; Said, Amal Saber (Journal of medical and pharmaceutical sciences, 2020)
Nutritional status has been played an important role in the effect on physical growth, cognitive development, and physical work capacity, and it consequently influences human performance and Heath. The study aims to examine the association between the results of educational tests and the nutritional status of School children.The methodology of the study included 150 school children in wadi eldawasir city, educational achievements were assessed by their score in mathematics, Arabic score, English score, Sciences score and Social score. Nutritional status was evaluated by anthropometric measurements, determining elements of the 24-hour recall of dietary intake, diet history. The most important results have shown that there are with respect to Arabic score, it correlated significantly positive with animal protein (p
Keywords: anthropometric measures; nutritional status; social and economic aspects; academic achievement; Wadi Al-Dawasir